2001
DOI: 10.1152/physrev.2001.81.2.629
|View full text |Cite
|
Sign up to set email alerts
|

The Oxytocin Receptor System: Structure, Function, and Regulation

Abstract: The neurohypophysial peptide oxytocin (OT) and OT-like hormones facilitate reproduction in all vertebrates at several levels. The major site of OT gene expression is the magnocellular neurons of the hypothalamic paraventricular and supraoptic nuclei. In response to a variety of stimuli such as suckling, parturition, or certain kinds of stress, the processed OT peptide is released from the posterior pituitary into the systemic circulation. Such stimuli also lead to an intranuclear release of OT. Moreover, oxyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
2,334
4
82

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,588 publications
(2,546 citation statements)
references
References 569 publications
47
2,334
4
82
Order By: Relevance
“…Second, it has been shown that in the rodent (Knobloch et al, 2012) and human brain (Boccia et al, 2013) there is a variety of “hard-wired” oxytocinergic nerve fibers from the hypothalamus to limbic, mesencephalic, and cortical brain regions that allow fine-tuned and fast modulation of target structures (Knobloch et al, 2012; Landgraf and Neumann, 2004; Stoop, 2012; Strathearn, 2011). Effects of OT in the CNS and in the periphery (e.g., heart and cardiovascular system, kidney, reproductive organs) are critically dependent on presence of OT receptors (OTR) (Gimpl and Fahrenholz, 2001). The OTR is a 389-amino acid polypeptide and belongs to the G-protein coupled receptor superfamily (Gimpl and Fahrenholz, 2001; Kimura et al, 1992).…”
Section: Ot and Early-life Stress (Els) – Role In Shaping Neural Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, it has been shown that in the rodent (Knobloch et al, 2012) and human brain (Boccia et al, 2013) there is a variety of “hard-wired” oxytocinergic nerve fibers from the hypothalamus to limbic, mesencephalic, and cortical brain regions that allow fine-tuned and fast modulation of target structures (Knobloch et al, 2012; Landgraf and Neumann, 2004; Stoop, 2012; Strathearn, 2011). Effects of OT in the CNS and in the periphery (e.g., heart and cardiovascular system, kidney, reproductive organs) are critically dependent on presence of OT receptors (OTR) (Gimpl and Fahrenholz, 2001). The OTR is a 389-amino acid polypeptide and belongs to the G-protein coupled receptor superfamily (Gimpl and Fahrenholz, 2001; Kimura et al, 1992).…”
Section: Ot and Early-life Stress (Els) – Role In Shaping Neural Cmentioning
confidence: 99%
“…Effects of OT in the CNS and in the periphery (e.g., heart and cardiovascular system, kidney, reproductive organs) are critically dependent on presence of OT receptors (OTR) (Gimpl and Fahrenholz, 2001). The OTR is a 389-amino acid polypeptide and belongs to the G-protein coupled receptor superfamily (Gimpl and Fahrenholz, 2001; Kimura et al, 1992). The OTR expressing gene ( OXTR ) is located on chromosomal region 3p25–3p26.2, spans 17 kb, and consists of 3 introns and 4 exons (Gimpl and Fahrenholz, 2001).…”
Section: Ot and Early-life Stress (Els) – Role In Shaping Neural Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Das Nonapeptid Oxytocin ist nach den altgriechischen Wörtern "ὀξύς" und "τόκος" benannt, was "schnelle Geburt" bedeutet, da es mit der uteruskontrahierenden Wirkung von Oxytocin zunächst in Verbindung gebracht wurde [29]. Oxytocin wird vornehmlich in den hypothalamischen Kernen PVN und Nucleus supraopticus (SON) produziert [29].…”
Section: Oxytocin Und Angstunclassified
“…As stated in the introduction, these enzyme immunoassay‐based findings could be due to the cross‐reactivity of molecules other than oxytocin 12, but it is also possible that the detected molecules were indeed oxytocin from a central or even a local origin. The hypothalamus is not the only site that produces oxytocin molecules, as endothelial and epithelial cells at various other sites throughout the body have been reported to produce it 26. Perhaps Kangaroo care and maternal scent are stimuli causing a local oxytocin release.…”
Section: Discussionmentioning
confidence: 99%